(untitled) (Journal of Medical & Health Sciences Review, 2025)
This qualitative study explored the experiences of undergraduate medical students participating in flipped classroom sessions, focusing on engagement, knowledge retention, and self-directed learning. A phenomenological approach was employed to capture students perceptions through semi-structured interviews, focus group discussions, classroom observations and reflective journals. Data analysis revealed that pre-class preparation combined with interactive in-class activities enhanced participation, improved knowledge retention and promoted self-directed learning. Students reported increased confidence in applying theoretical knowledge to clinical scenarios and demonstrated active engagement in collaborative problem-solving exercises. However, some participants faced challenges such as time constraints, initial resistance to the new format, and the need for clear guidance from instructors. Despite these challenges, students adapted over time, indicating the model’s potential for effective learning in health professional education. These findings provide practical insights for educators seeking to implement flipped classroom strategies, highlighting the importance of structured guidance, adequate resources, and supportive learning environments. The study underscores the potential of flipped learning to foster active, autonomous, and application-oriented learning among health professional students.